2012
DOI: 10.1080/10665684.2012.719424
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Students for Social Action in a Social Justice Education Course: What Works?

Abstract: The purpose of this study was to explore students' perceptions of how the curriculum and teaching strategies in a social justice education course prepared them for social action engagement. Past studies using a similar approach to teaching about social justice issues did not include student interviews. Students' perspectives can shed light on how experiences in a social justice education course prepared them to challenge social oppression and work toward equity in their daily lives. Six students were interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…El peligro de no atender a esta demanda podría profundizar los efectos negativos, ya que como señala Burrell (2012), "lack of experience with diversity can cause misunderstandings among social groups, especially if the information learned about one another comes from unreliable sources that perpetuate stereotypes, prejudice, and bias [la falta de experiencia con la diversidad puede causar falta de comprensión entre grupos sociales, especialmente si la información aprendida sobre los otros viene de fuentes no confiables que perpetúan los estereotipos, el prejuicio y el sesgo]" (p. 547).…”
Section: Discusión Y Conclusionesunclassified
“…El peligro de no atender a esta demanda podría profundizar los efectos negativos, ya que como señala Burrell (2012), "lack of experience with diversity can cause misunderstandings among social groups, especially if the information learned about one another comes from unreliable sources that perpetuate stereotypes, prejudice, and bias [la falta de experiencia con la diversidad puede causar falta de comprensión entre grupos sociales, especialmente si la información aprendida sobre los otros viene de fuentes no confiables que perpetúan los estereotipos, el prejuicio y el sesgo]" (p. 547).…”
Section: Discusión Y Conclusionesunclassified
“…Accordingly, some scholars suggest a need for increased inclusion of social justice theories and application in academic curricula. This could be helpful given the negative impact on people and families created by disparities and oppressions that continue to exist (e.g., Pittman, ; Storms, ). While social justice, which has been strongly influenced by the fields of feminism, multiculturalism, and interdisciplinary studies, has given birth to these need‐based calls (Goodman et al., ; Mallinckrodt, Miles, & Levy, ), research has found that experiential learning such as service learning and internships has the capacity to promote strong social justice outcomes among students (Gillis & Lellan, 2010; Storms, ).…”
mentioning
confidence: 99%
“…2004; Mallinckrodt, Miles, & Levy, 2014), research has found that experiential learning such as service learning and internships has the capacity to promote strong social justice outcomes among students (Gillis & Lellan, 2010;Storms, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For one, while the administrative aspects of social justice have been addressed in these studies, its class-based aspects have remained largely ignored. International studies on social justice, by contrast, have focused on school administrators (Bruccoleri, 2008), the development of social justice curriculum (Henderson, 2009), preservice teachers (Lee, 2011), and student perceptions (Storms, 2012). Meanwhile, other research has examined social studies teachers' perceptions and experiences of social justice (Bender-Slack & Raupach 2008;Samuels, 2014) and their in-class practices (Good, 2010;Philpott, 2009;Robertson, 2008).…”
Section: Introductionmentioning
confidence: 99%